2004
DOI: 10.1242/dev.01148
|View full text |Cite
|
Sign up to set email alerts
|

Unique and overlapping functions of pRb and p107 in the control of proliferation and differentiation in epidermis

Abstract: The retinoblastoma gene product, pRb, plays a crucial role in cell cycle regulation, differentiation and inhibition of oncogenic transformation. pRb and its closely related family members p107 and p130 perform exclusive and overlapping functions during mouse development. The embryonic lethality of Rb-null animals restricts the phenotypic analysis of these mice to mid-gestation embryogenesis. We employed the Cre/loxP system to study the function of Rb in adult mouse stratified epithelium. RbF19/F19;K14cre mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
197
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(219 citation statements)
references
References 62 publications
(80 reference statements)
18
197
4
Order By: Relevance
“…Nevertheless, all these defects appeared more severe in the co-absence of p107, indicating that p107 can partially compensate for Rb loss in the epidermis. By contrast, in the skin lacking only p107 and pRb2/p130, Ruiz et al (2004) observed that the initial differentiation step was unaffected, whereas worthy defects in terminal differentiation existed. These results demonstrate that pRb and p107 functions in epidermis overlap only partially, as they also show different abilities in suppressing hyperplasia and in regulating skin differentiation.…”
Section: Differences Between Rb Family Membersmentioning
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, all these defects appeared more severe in the co-absence of p107, indicating that p107 can partially compensate for Rb loss in the epidermis. By contrast, in the skin lacking only p107 and pRb2/p130, Ruiz et al (2004) observed that the initial differentiation step was unaffected, whereas worthy defects in terminal differentiation existed. These results demonstrate that pRb and p107 functions in epidermis overlap only partially, as they also show different abilities in suppressing hyperplasia and in regulating skin differentiation.…”
Section: Differences Between Rb Family Membersmentioning
confidence: 80%
“…It has been revealed that Rb2/p130 could also contribute to G1 arrest through its unique spacer region, which grants the ability to suppress cdk2 kinase activity, thereby decreasing the activity of kinases that allow the cell to enter S-phase (De Luca et al, 1997). Furthermore, according to several studies using fibroblasts from knockout mouse embryos, the deficiency of Rb or of more than one family member exhibits a shortened G1 phase of the cell cycle and subsequent lengthening of S phase (Ruiz et al, 2004). The binding of Rb family proteins with the E2F family of transcription factors seems to be pivotal in leading cell cycle progression and DNA replication by determining the expression of cell cycle E2F-dependent genes (Frolov and Dyson, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, the loss of Rb appears to disrupt the coordination between cell cycle exit and differentiation. In RbÀ/À skin for example, suprabasal keratinocytes continued to divide even though they lost expression of basal keratins and induced expression of more differentiated keratin (Ruiz et al, 2004). In sensory hair cells of the ear, Rb is normally upregulated during terminal differentiation, but when Rb is removed there is increased proliferation not only of the proliferating progenitors but also of the normally postmitotic, differentiated cells (Sage et al, 2005).…”
Section: The Role Of Rb In Differentiationmentioning
confidence: 99%
“…Oncoproteins E6 and E7, translated products of HPV DNA integrated into the genome of the host epithelial cell, are capable of inducing oncogenesis via multiple mechanisms, including E6-induced degradation of p53 and E7-mediated loss of the retinoblastoma protein tumorsuppressorfunction [14][15][16][17][18][19]. Also, p16 has been determined to be a surrogate marker for HPV inlocallyadvancedanalcarcinoma [20].Aclearassociationbetween altered immunity and the development of SCCA is apparent, and a functional immune system is likely responsible for clearing HPV infection.…”
Section: Introductionmentioning
confidence: 99%